2013
DOI: 10.1007/s00204-013-1170-x
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic mixtures and dissimilar action: concepts for prediction and assessment

Abstract: Combinations of genotoxic agents have frequently been assessed without clear assumptions regarding their expected (additive) mixture effects, often leading to claims of synergisms that might in fact be compatible with additivity. We have shown earlier that the combined effects of chemicals, which induce micronuclei (MN) in the cytokinesis-block micronucleus assay in Chinese hamster ovary-K1 cells by a similar mechanism, were additive according to the concept of concentration addition (CA). Here, we extended th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 26 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…For this reason, Kocaman and Topaktas (2010) discourage application of CA and IA models for the prediction of genotoxicity of mixtures. In contrast, other studies showed the applicability of CA and IA for investigating the genotoxic potential of anticancer mixtures (Ermler et al 2014;Mater et al 2014). …”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…For this reason, Kocaman and Topaktas (2010) discourage application of CA and IA models for the prediction of genotoxicity of mixtures. In contrast, other studies showed the applicability of CA and IA for investigating the genotoxic potential of anticancer mixtures (Ermler et al 2014;Mater et al 2014). …”
Section: Resultsmentioning
confidence: 94%
“…Indeed, different from ecotoxicity tests where there was a clear concentration-response relationship with a sigmoidal-shaped curve (0-100 % effect), in genotoxicity tests, such as the comet and micronucleous assays, this relationship is more variable. It has to be taken into account that spontaneous DNA damage occurs detected in these assays as a baseline response above zero, while at high exposure levels, cytotoxicity could occur interfering with the genotoxic response (Ermler et al 2014). For this reason, Kocaman and Topaktas (2010) discourage application of CA and IA models for the prediction of genotoxicity of mixtures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the application of mathematical models to ascertain genotoxic interactive effects, similarly to what has been done for combined cytotoxicity assessment, is highly relevant to have firm and reliable conclusions about genotoxic interactive effects. In this sense, Ermler et al (2014) have already shown that the CA, IA and hybrid CA/IA models are applicable to data obtained for several model compounds with similar and dissimilar MoA, using the micronucleus assay.…”
Section: Evaluation Of Combined Effects Of Multiple Mycotoxinsmentioning
confidence: 92%
“…If some chemicals produce the effect by similar mechanisms, the principles of independence of action are not met anymore, and it is likely that observed mixture effects deviate somewhat from those predicted by the independent action concept. A recent paper examining the joint effects of several substances producing micronuclei through different modes of action has given indications that the number of different mechanisms available for the induction of this effect is smaller than the number of chemicals capable of producing this kind of toxicity (Ermler et al, 2013b).…”
Section: The Role Of Mode Of Action Information In Guiding a Priori Cmentioning
confidence: 99%